What are the believes, spiritual, subcultural, religious, traditional, and family structure of perpetrators of domestic violence? A question for further studies - Shahrbanoo Ghahari; Saeed Imani; Jafar Bolhari (Shahid Beheshti University of Medical Sciences, 2017)
What is believes, spiritual, subcultural, religious, traditional, and family structure of Perpetrators of  domestic violence? A question for further studies